2022
DOI: 10.3390/diagnostics12112621
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ultrasonographic Anthropometric-Independent Measurement of Median Nerve Swelling in Carpal Tunnel Syndrome: The “Nerve/Tendon Ratio” (NTR)

Abstract: Background: There is little consensus on ultrasound (US) normative values of cross-sectional area of median nerve (MN-CSA) in carpal tunnel syndrome (CTS) because of its dependency on anthropometric parameters. We aim to propose a novel anthropometric-independent US parameter: MN-CSA/flexor radialis carpi CSA (FCR-CSA) ratio (“Nerve Tendon Ratio”, NTR), in the diagnosis of clinically and electrodiagnostic (EDS)-defined CTS. Methods: 74 wrists of 49 patients with clinically defined CTS underwent EDS (scored by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In a study conducted in a non-pregnant population, NTR was found to be 0.83%. 23 Especially, the origin of this parameter stems from the search for a new parameter independent of anthropometric measurements, as wrist measurements in CTS are influenced by wrist thickness and a person's height and weight measurements. In this context, it is promising as a new parameter in the face of differences in weight and edema between trimesters in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in a non-pregnant population, NTR was found to be 0.83%. 23 Especially, the origin of this parameter stems from the search for a new parameter independent of anthropometric measurements, as wrist measurements in CTS are influenced by wrist thickness and a person's height and weight measurements. In this context, it is promising as a new parameter in the face of differences in weight and edema between trimesters in pregnant women.…”
Section: Discussionmentioning
confidence: 99%